Advancing Technology-Enhanced Learning: A Systematic Literature Review of Innovative Frameworks and Emerging Technologies for Education 4.0 - Khupe, Derrick; Zlotnikova, Irina; Hlomani, Hlomani (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Education 4.0 (Edu 4.0) is an evolving paradigm that aligns education systems with the demands of Industry 4.0 by integrating emerging technologies (ETs) such as artificial intelligence, the Internet of Things, and extended reality into teaching and learning. This paper presents a systematic literature review (SLR) of 19 peer-reviewed frameworks and models published between 2020 and 2024 that incorporate ETs within the Edu 4.0 context. This study examines the characteristics of these frameworks, the technologies they adopt, and the pedagogical strategies they support. The findings reveal dominant trends in AI and IoT use, a growing reliance on personalized and adaptive learning, and underutilization of advanced technologies such as digital twins and quantum computing. Key gaps include limited attention to primary and secondary education, equity, accessibility, and ethical considerations. In response, a preliminary conceptual framework is proposed to guide the inclusive and scalable implementation of Edu 4.0. This study offers actionable insights for educators, researchers, and policymakers aiming to build future-ready, ethically grounded, and context-sensitive education systems that harness the full potential of technological innovation.